Pinecone 1975 - Valdosta State College (Valdosta State College, 1975)
There are many different types of people in the world, all with their own looks, dress, and mannerisms. But when you strip away all the frivolous differences you will find that all people are basically the same, guided by the same emotions, desires, and prejudices. VSC is no different than any other place in the world; we too are made up of many different types of people. Here at VSC, as elsewhere, no two people are alike, yet no two people are totally different. 101213Each Individual has his own method of expressing himself to others. Some use dance, others song and still others just what they say or the expression on their faces. And of course photographers have a method all their own?! 15I pride myself on being myself Do not fault me for that but admire me instead I am unique, different, set apart from others I am black, I am white, I am man, I am woman but above all else, I am what I am. Before we can know others we must know ourselves. Who am I? What do I want? Why am I here? These are the questions we must answer for our Come out from hiding and be yourself.Valdosta State College 1975 Pine Cone Valdosta, Georgia Volume LXII
A yearbook was published for Valdosta State College from 1925-1977, under the name The Pinecone. From 1981-1987, a yearbook was published called Milestones. Valdosta State University had three names during this period, Georgia State Womans College, 1925-1950; Valdosta State College, 1950-1993; and Valdosta State University 1993-present.
Keywords: yearbook; Americana; University History